Penerapan metode Balanced scorecard dalam industri pariwisata pasca Pandemi Covid-19: Literature Review - Ekalia Yanasari Putri; Fajar Hayyin; Saefullah Saefullah (Universitas Mercu Buana, 2020)
The balanced scorecard (BSC) still receives great attention, both by researchers and business people in various fields, one of which is the tourism business. The paper aims to analyze the application of the BSC in order to increase the potential revenue of the tourism sector while reducing potential losses. This study departs on the concern of the condition of the Indonesian people in the midst of the COVID-19 pandemic, where the impact of COVID-19 is strongly felt in the tourism services sector, Hotel, Tour & Travel, Restaurant and Park Industry. The study was conducted based on a systematic literature review, scientific data taken from various journals published in 2016 - 2020, then analyzed quantitatively to assess the significance of the relationship between contingency factors and the use of BSC. The results confirm previous studies which show that the use of BSC is biased towards larger companies, but is effective in smaller industries. Qualitative analysis combines these results which show that the BSC is used primarily to align goals and improve business processes and communication in organizations.